Breast and gynecological cancers an integrated approach for screening and early diagnosis in developing countries - Shetty, Mahesh K (Springer New York, 2013)
Women in developing nations experience higher incidence rates and higher mortality rates of breast and gynecological cancers, creating a critical need for cancer control programs that can use available, often scant, resources to match the existing disease burden. This book promotes integrating screening and early detection of breast and gynecological cancers through cost effective modalities like single visit screening and diagnosis, well woman clinics, and mobile clinics.  International experts in the field weigh in on tested and proven methods for screening, early diagnosis, and prevention of these cancers in both rural and urban settings with varying levels of funding.  Case studies from Brazil, Peru, the Middle East and Africa are included to illustrate particular aspects of screening, treatment, and funding. Breast and Gynecological Cancers: An Integrated Approach for Screening and Early Diagnosis in Developing Countries is a crucial compendium of information for all those concerned with the wellness of women worldwide.